Widespread lithogenic control of marine authigenic neodymium isotope records? Implications for paleoceanographic reconstructions - Abbott, A. N.; Löhr, S. C.; Payne, A.; Kumar, H.; J. Du (Geochimica et Cosmochimica Acta, 2022)
Our understanding of past ocean-climate dynamics is informed by multiple paleocirculation proxies including δ13C, 231Pa/230Th, and radiogenic neodymium isotopes (εNd). Of these, the εNd signature of marine authigenic phases is of particular importance as it is considered a robust circulation proxy applicable across timescales, permitting circulation reconstructions during periods of rapid, climatically-induced biological or chemical change (e.g. productivity, pH). However, growing evidence of non-conservative behavior and a widespread sedimentary source (benthic flux via pore water) of Nd to the global ocean suggests that authigenic εNd records do not strictly record a water mass signature, highlighting the need to reconsider interpretations of the authigenic record. To examine the impact of a sedimentary influence on the authigenic record, here we compile paired authigenic and detrital neodymium records from every major ocean basin and from 80 Ma to present. We then focus on just the North Atlantic Ocean basin to examine if this relationship holds up regionally and how authigenic εNd changes relate to sediment composition changes from two scientific ocean drill cores spanning the past 25 ka. We present a new conceptual framework to guide our discussion that examines the coupling or decoupling of authigenic and detrital εNd in terms of the relative importance of each of the three major potential controls as defined in the existing literature (bottom water, pore water, sediments) on the authigenic record. Our compilation reveals a strong linear relationship between detrital εNd and authigenic εNd (correlation coefficient = 0.86, n = 871), demonstrating a widespread influence of lithogenically sourced neodymium on authigenic εNd. We find the same is true within the North Atlantic, with the authigenic records at both locations strongly influenced by the sediments and likely not recording bottom water neodymium values. Emerging evidence for a lithogenic or benthic flux influence on the budgets of a wide range of trace elements suggests that our interpretative framework will be broadly useful for understanding the behavior of trace elements and their isotopes at the sediment-water interface.
Keywords: Benthic flux; Neodymium isotopes; Paleoceanography; Pore water; Rare Earth Elements